Komparasi Hasil Belajar Pendidikan Teknik Elektro Berdasarkan Latar Belakang Pendidikan dan Jalur Masuk - Apeldo, Vandy; Taali, Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This research is motivated by the low academic performance of students in the Applied Mathematics course. Students admitted through the SNMPTN pathway show lower learning outcomes compared to those admitted through the SBMPTN and Mandiri pathways. These differences in academic performance are concerning, as they may reflect the influence of educational background and admission pathways on students' academic readiness. Therefore, this study aims to analyze differences in student learning outcomes in the Applied Mathematics course within the Electrical Engineering Education Study Program at Universitas Negeri Padang, class of 2022, based on educational background (high school and vocational school) and university entrance pathways (SNMPTN, SBMPTN, and Mandiri). This research employs a quantitative approach with a comparative method. Data were collected through documentation of student grades and analyzed using descriptive and inferential statistical techniques. The findings indicate that there is no significant difference in learning outcomes based on educational background and university entrance pathways. The results suggest that factors other than educational background and admission pathways may play a more dominant role in determining students' academic performance in the Applied Mathematics course.